Method for rapidly preparing SSZ-13 molecular sieve membrane in active sol and application of molecular sieve membrane
By strengthening sol aging and optimizing the OSDA/SiO2 ratio, the problem of nucleation and long crystal growth cycle of SSZ-13 molecular sieve membrane is solved, and the rapid preparation of high-throughput and high-selectivity SSZ-13 molecular sieve membrane is achieved. It is suitable for the separation of CO2/CH4 and CO2/N2 mixed gases, and has industrial prospects.
Patent Information
- Application Number
- CN202510545392.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-07-25
AI Technical Summary
In the existing preparation method of SSZ-13 molecular sieve membrane, the nucleation and crystal growth periods are long, which makes it difficult to control the thickness and uniformity of the membrane layer. The sol nucleates and grows inside the porous carrier pore, increasing mass transfer resistance and affecting the gas permeability rate.
By strengthening the sol aging process and optimizing the OSDA/SiO2 ratio, the reaction sol activity is improved, and the rapid nucleation and dominant growth of the sol on the surface of the porous support are promoted, and high-throughput and highly selective SSZ-13 molecular sieve membrane is prepared.
The rapid film formation of SSZ-13 molecular sieve membrane is achieved, and a dense continuous film can be produced in only 2-10 hours, significantly improving the gas separation performance, and is suitable for natural gas purification and flue gas carbon capture.
Smart Images

Figure CN120361739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol and application of the molecular sieve membrane, belonging to the technical field of molecular sieve membrane material preparation. Background Art
[0002] Membrane separation technology is an emerging separation technology with the advantages of good separation effect, simple operation, small footprint, low energy consumption, low production cost, and no pollution to the environment. It is widely used in petrochemical, wastewater treatment, medical care, metallurgy, food and other fields. As a new type of inorganic membrane material, molecular sieve membrane has excellent thermal stability and chemical stability, high mechanical strength, and regular molecular size pore structure, becoming a research hotspot and frontier in the field of membrane technology. At present, the preparation of defect-free, stable, high-flux and high-selectivity molecular sieve membranes has become a research topic of common concern at home and abroad. Among them, SSZ-13 molecular sieve membranes are the most widely studied. SSZ-13 molecular sieve membranes have three-dimensional octahedral pores with a size of 0.38×0.38nm. SSZ-13 molecular sieve membranes have the characteristics of preferential adsorption of CO2, and their pore size is between CO2 and N2 and CH4. Therefore, they are used in carbon capture of natural gas and flue gas represented by CO2 / CH4 and CO2 / N2.
[0003] In the existing preparation method of SSZ-13 molecular sieve membrane, the nucleation and crystal growth cycle of SSZ-13 is long, and the synthesis time usually takes up to 2-5 days, which makes it difficult to control the thickness and uniformity of the membrane layer; at the same time, the sol that penetrates into the pores of the carrier is fully nucleated and grows to form a large number of crystals during the long film formation cycle, which significantly increases the mass transfer resistance of the overall membrane and seriously affects the gas permeation rate of the membrane. Increasing the crystallization rate of the membrane layer can effectively reduce the growth of crystals inside the support, so that the growth on the surface of the carrier has a competitive advantage and a higher flux SSZ-13 molecular sieve membrane is obtained.
[0004] Currently, a variety of methods for the rapid synthesis of SSZ-13 zeolite molecular sieve membranes have been developed. The research focuses mainly on the optimization of heat transfer methods, such as oil bath heating and microwave-assisted heating, aiming to quickly reach the reaction active temperature through heat transfer enhancement, thereby shortening the membrane growth cycle. However, the above methods still have difficulty solving the problem of high mass transfer resistance caused by the symbiosis of SSZ-13 molecular sieves on the surface of porous carriers and inside the pores due to insufficient sol activity. Because the nucleation and crystallization growth mechanism of zeolite molecular sieves is still unclear, the film formation mechanism of molecular sieve membranes is more complicated, and the reference value of different types of molecular sieves and molecular sieve membranes is very small. How to control the efficient nucleation of the reaction sol and achieve controllable growth of membrane crystals is a challenge and difficulty in research in this field. Summary of the invention
[0005] The object of the present invention is to provide a method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol and the application of the molecular sieve membrane. By strengthening the sol aging process and regulating the synthesis ratio, the activity of the reaction sol is improved, the rapid nucleation and preferential growth of the sol on the surface of the porous support are promoted, the rapid film formation of the SSZ-13 molecular sieve is realized, and a high-throughput and highly selective SSZ-13 molecular sieve membrane is obtained.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol is to first mix a silicon source, an alkali source, an aluminum source, an organic structure-directing agent (OSDA) and a solvent to form a sol, then age it at room temperature to obtain an active sol; then place a porous support coated with a seed layer in the active sol, and after hydrothermal reaction, wash, dry and calcine to obtain an SSZ-13 molecular sieve membrane.
[0008] Preferably, the molar composition of the sol is:
[0009] SiO2:NaOH:Al(OH)3:OSDA:H2O = 1:(0.2 - 0.8):(0.01 - 0.2):(0.1 - 1):(10 - 800).
[0010] Preferably, the silicon source is tetraethyl orthosilicate, tetramethyl orthosilicate, sodium silicate, water glass or silicon powder.
[0011] Preferably, the alkali source is lithium hydroxide, sodium hydroxide, potassium hydroxide or cesium hydroxide.
[0012] Preferably, the aluminum source is aluminum hydroxide, sodium aluminate, boehmite, aluminum isopropoxide, aluminum butoxide, aluminum foil, aluminum powder or alumina.
[0013] Preferably, the organic structure-directing agent is one or more of N-N-N-trimethyladamantyl ammonium hydroxide, N-N-N-trimethyladamantyl ammonium bromide, N-N-N-trimethyladamantyl ammonium iodide and tetraethyl ammonium hydroxide.
[0014] Preferably, the aging duration is 1 - 8 d.
[0015] Preferably, the hydrothermal reaction conditions are: 110 - 200 °C, 2 - 10 h.
[0016] Preferably, the calcination atmosphere is air, oxygen or ozone; the temperature is 150 - 500 °C, the calcination time is 5 - 72 h, and the heating rate is 0.2 - 5 °C / min.
[0017] Preferably, the material of the porous support is at least one of alumina, zirconia, titania, mullite, silicon carbide and silica.
[0018] Application of the SSZ-13 molecular sieve membrane prepared by any of the above methods in CO2 separation. The membrane has good separation performance for CO2 / CH4 and CO2 / N2 mixed gases and is applicable to natural gas purification and carbon capture from flue gas.
[0019] The beneficial effects of the present invention are as follows:
[0020] By strengthening the sol aging process, the nucleation density is increased to improve the synthesis microenvironment of the membrane and enhance the activity of the synthesized sol; and by optimizing the OSDA / SiO2 ratio, the quality of the synthesized membrane is increased and the membrane preparation cycle is shortened. A dense and continuous SSZ-13 molecular sieve membrane can be prepared in only 2 - 10 h. Moreover, the prepared SSZ-13 molecular sieve membrane has high repeatability and exhibits excellent separation performance in the CO2 separation of CO2 / CH4 and CO2 / N2 mixtures, has the prospect of industrial development, and is applicable to natural gas purification and carbon capture from flue gas. Description of the Drawings
[0021] Figure 1 (a) Scanning electron microscope image of the surface of the SSZ-13 molecular sieve membrane prepared in Example 1; (b) Scanning electron microscope image of the cross-section of the membrane layer;
[0022] Figure 2 X-ray diffraction pattern of the SSZ-13 molecular sieve membrane prepared in Example 1;
[0023] Figure 3 Schematic structural diagrams of the single-channel, 7-channel or 19-channel carriers used in the examples and comparative examples. Detailed Embodiments
[0024] Example 1
[0025] A method for rapidly preparing a high-performance SSZ-13 molecular sieve membrane in an active sol, the steps of which are as follows:
[0026] Mix an aqueous solution of silica, sodium hydroxide, aluminum hydroxide, N-N-N-trimethyl-1-adamantyl ammonium hydroxide and deionized water in a certain proportion to form a sol (molar composition: 1SiO2:0.2NaOH:0.01Al(OH)3:0.4OSDA:44H2O, where the OSDA / SiO2 ratio is 0.4), and then age at room temperature for 8 d to form a uniform active sol.
[0027] The single-channel support coated with seeds (an asymmetric alumina tube single-channel support with an outer tube diameter of 10 mm, an inner tube diameter of 7 mm, a tube length of 6 mm, and an average pore diameter of 200 nm) was vertically placed in a polytetrafluoroethylene reactor containing the above-mentioned active sol, and a synthesis reaction was carried out at 200 °C for 2 h. After the reaction, it was washed, dried at 100 °C, and calcined in an ozone atmosphere to remove OSDA. The calcination temperature was 200 °C, the calcination time was 72 h, and the heating rate was 3 °C / min. After calcination, an SSZ-13 zeolite membrane was obtained, and the prepared membrane was labeled as M1.
[0028] Figure 1 In Figure a, the scanning electron microscope image of the surface of the prepared SSZ-13 zeolite membrane is shown, and in Figure b, the scanning electron microscope image of the cross-section of the membrane layer of the prepared SSZ-13 zeolite membrane is shown. Figure 1 It can be seen that the grown membrane layer is dense and continuous without obvious defects, and the membrane layer thickness is about 2.9 μm. Figure 2 Figure is the X-ray diffraction pattern of the prepared SSZ-13 zeolite membrane. The X-ray diffraction pattern indicates that the synthesized zeolite membrane is a pure phase of SSZ-13.
[0029] Example 2
[0030] It is basically the same as Example 1, except that the support used in Example 2 is a bare single-channel support without coating seeds. The prepared membrane is denoted as M2.
[0031] Example 3
[0032] It is basically the same as Example 1, except that in the molar composition of the sol, the OSDA / SiO2 ratio is 0.3. The prepared membrane is denoted as M3.
[0033] Example 4
[0034] It is basically the same as Example 1, except that the sol is not subjected to an aging treatment. The prepared membrane is denoted as M4.
[0035] Example 5
[0036] It is basically the same as Example 1, except that the aging time of the sol is 3 d. The prepared membrane is denoted as M5.
[0037] Example 6
[0038] It is basically the same as Example 1, except that the synthesis reaction temperature is 180 °C. The prepared membrane is denoted as M6.
[0039] Example 7
[0040] Basically the same as Example 1, except that OSDA was removed by calcination in an air atmosphere, the calcination temperature was 480 °C, the calcination time was 72 h, and the heating rate was 0.5 °C / min. The prepared membrane was labeled as M7.
[0041] Example 8
[0042] Basically the same as Example 1, except that the synthesis reaction time was 4 h. The prepared membrane was denoted as M8.
[0043] Comparative Example 1
[0044] Basically the same as Example 1, except that the molar composition of the sol was: 1SiO2:0.2NaOH:0.01Al(OH)3:0.2OSDA:40H2O, and the aging time was 6 h. The prepared membrane was labeled as M9.
[0045] Comparative Example 2
[0046] Basically the same as Example 1, except that the molar composition of the sol was: 1SiO2:0.2NaOH:0.01Al(OH)3:0.2OSDA:40H2O; the synthesis temperature was 180 °C, and the synthesis time was 72 h. The prepared membrane was labeled as M10.
[0047] The structural schematic diagrams of the single-channel, 7-channel or 19-channel carriers used in the examples and comparative examples are as shown in Figure 3 regions a, b, and c in
[0048] The gas separation performance of the molecular sieve membrane was tested with an equimolar ratio of CO2 / CH4 mixed gas or an equimolar CO2 / N2 mixed gas, and was represented by two parameters: the gas permeation rate P and the separation selectivity S. Among them, the gas permeation rate P represents the total amount of gas passing through a unit membrane area per unit time and per unit pressure, P = N / (A×t×△P), with the unit of mol / (m 2 sPa); the separation selectivity S is used to evaluate the membrane separation efficiency, S = P A / P B . In the formula, P A and P B represent the permeation rates of the gas on the permeate side and the feed side, respectively.
[0049] The prepared membrane was tested for gas separation performance in the CO2 / CH4 system. The test conditions were as follows: temperature 25°C, transmembrane pressure drop 0.2 MPa, permeate side pressure maintained at 0.103 MPa, CO2 / CH4 molar composition 50 / 50%, and feed gas flow rate 4 L / min. The gas flow rate on the permeate side was measured by a soap bubble flowmeter, and the gas composition on the permeate side was analyzed by a gas chromatograph (Shimadzu, GC2014). The test results are shown in Table 1.
[0050] Table 1 CO2 / CH4 Mixed Gas Separation Performance of SSZ-13 Zeolite Membrane
[0051]
[0052] The prepared membrane was tested for gas separation performance in the CO2 / N2 system. The test conditions were as follows: temperature 25°C, transmembrane pressure drop 0.2 MPa, permeate side pressure maintained at 0.103 MPa, CO2 / N2 molar composition 50 / 50%, and feed gas flow rate 4 L / min. The gas flow rate on the permeate side was measured by a soap bubble flowmeter, and the gas composition on the permeate side was analyzed by a gas chromatograph (Shimadzu, GC2014). The test results are shown in Table 2.
[0053] Table 2 CO2 / N2 Mixed Gas Separation Performance of SSZ-13 Zeolite Membrane
[0054]
[0055] By analyzing the strengthening effect of the sol aging process through the above process, a comparison was made between Example 1 (aged for 8 days) vs Example 4 (not aged) vs Example 5 (aged for 3 days). It can be seen that: M1 (Example 1): CO2 permeation rate 32.6×10 -7 mol / (m 2 s Pa), separation selectivity 697; M4 (Example 4, not aged): There were defects in the membrane layer, which was not dense and complete, resulting in no separation selectivity; M5 (Example 5, aged for 3 days): There were also large membrane layer defects and no gas separation selectivity. Due to insufficient aging (M4, M5), the nucleation density of the sol was low, and a dense and continuous membrane layer could not be formed. The competition between nucleation on the carrier surface and crystal growth inside the pores was unbalanced, ultimately leading to membrane defects; while sufficient aging (M1) increased the nucleation density, optimized the synthesis microenvironment, promoted preferential nucleation on the carrier surface, formed a defect-free membrane layer, and at the same time inhibited excessive crystal growth inside the pores and reduced the mass transfer resistance.
[0056] Analysis of the optimization of the OSDA / SiO₂ ratio through the above process. From Example 1 (OSDA / SiO₂ = 0.4) vs Example 3 (OSDA / SiO₂ = 0.3) vs Comparative Example 1 (OSDA / SiO₂ = 0.2), it can be seen that for M1 (OSDA / SiO₂ = 0.4), the CO₂ permeation rate is the highest and the selectivity is the best; for M3 (OSDA / SiO₂ = 0.3), the permeation rate drops to 10.6×10 -7 mol(m 2 s Pa) -1 , the selectivity is 136, and the performance drops significantly; while for M9 (Comparative Example 1, OSDA / SiO₂ = 0.2), the film layer has large defects and is not continuous and dense, resulting in no gas separation selectivity. It can be seen that when the OSDA / SiO₂ ratio is too low, the nutrients are insufficient to form a continuous and dense membrane (M3, M9), weakening the structure-directing effect, leading to disordered crystal growth and incomplete pore structures. Optimizing OSDA / SiO₂ = 0.4 (M1) forms a regular CHA cage structure by balancing charge guidance and framework growth, enhancing the CO₂ selective adsorption capacity.
[0057] Analysis of the significant reduction in the preparation period through the above process. From Example 1 (2 hours) vs Comparative Example 2 (72 hours), it can be seen that for M1 (2 hours), the CO₂ permeation rate is 32.6×10 -7 mol(m 2 s Pa) -1 , and the selectivity is 697. For M10 (Comparative Example 2, 72 hours), the permeation rate is only 10×10 -7 mol(m 2 s Pa) -1 , and the selectivity is 136. Therefore, it can be seen that long-time synthesis (M10) leads to excessive nucleation of the sol inside the carrier pores, crystal blockage of the pores, increased mass transfer resistance, and reduced permeation rate; short-time optimization (M1) achieves high throughput by the efficient nucleation of the active sol, preferentially forming a dense film layer quickly on the carrier surface to avoid pore blockage.
[0058] The above are only the preferred embodiments of the present invention patent. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention patent, several improvements and refinements can still be made, and these improvements and refinements should also be regarded as the protection scope of the present invention patent.
Claims
1. A method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol, characterized in that, First, a silicon source, an alkali source, an aluminum source, an organic structure-directing agent (OSDA), and a solvent are mixed to form a sol with a molar composition of: SiO2:NaOH:Al(OH)3:OSDA:H2O = 1:(0.2 - 0.8):(0.01 - 0.2):(0.1 - 1):(10 - 800). Then, it is aged at room temperature for 1 - 8 days to obtain an active sol; Subsequently, a porous support coated with a seed layer is placed in the active sol. After hydrothermal reaction, it is washed, dried, and calcined to obtain an SSZ-13 zeolite membrane.
2. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, characterized in that, The silicon source is tetraethyl orthosilicate, tetramethyl orthosilicate, sodium silicate, water glass, or silicon powder.
3. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, characterized in that The alkali source is lithium hydroxide, sodium hydroxide, potassium hydroxide, or cesium hydroxide.
4. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, wherein The aluminum source is aluminum hydroxide, sodium aluminate, boehmite, aluminum isopropoxide, aluminum butoxide, aluminum foil, aluminum powder, or alumina.
5. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, wherein The organic structure-directing agent is one or more of N-N-N-trimethyladamantyl ammonium hydroxide, N-N-N-trimethyladamantyl ammonium bromide, N-N-N-trimethyladamantyl ammonium iodide, and tetraethyl ammonium hydroxide.
6. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, characterized in that The material of the porous support is at least one of alumina, zirconia, titania, mullite, silicon carbide, and silica.
7. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, characterized in that, The conditions of the hydrothermal reaction are: 110 - 200 °C, 2 - 10 h.
8. The method for rapidly preparing an SSZ-13 molecular sieve membrane in an active sol according to claim 1, characterized in that, The atmosphere for calcination is air, oxygen, or ozone; the temperature is 150 - 500 °C, the calcination time is 5 - 72 h, and the heating rate is 0.2 - 5 °C / min.
9. Application of the SSZ-13 zeolite membrane prepared by the method according to any one of claims 1 - 8 in CO2 separation.
Citation Information
Patent Citations
Method for rapidly synthesizing high-silicon SSZ-13 molecular sieve membrane
CN108579449A
Preparation method of all-silicon CHA molecular sieve membrane
CN114804146A